Документ, як засіб забезпечення ефективної роботи бібліотек - Кузик, Ірина; Мина, Жанна (Видавництво Львівської політехніки, 2020)
The extremely difficult tasks facing libraries today place important demands on their organization and management. An important means of effective library management is the availability of organizational and administrative, technological and scientific and methodological documentation, the quality of which significantly depends on the level of work organization and the degree of responsibility of employees.
Keywords: бібліотека; документ; організація; документаційне забезпечення; типова документація; профільна документація